2021
DOI: 10.1186/s12889-021-10565-7
|View full text |Cite|
|
Sign up to set email alerts
|

Weight stigma experiences and self-exclusion from sport and exercise settings among people with obesity

Abstract: Background A central strategy to tackle the health risks of obesity is regular physical activity (PA), exercising and participating in sports. However, people with obesity regularly experience weight-related stigma and discrimination in sport and exercise settings. Research has indicated that they often cope with such experiences by simply excluding themselves from sport and exercise. Meanwhile, self-exclusion as a coping strategy has not been fully understood and it remains unclear to what ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 62 publications
3
17
1
2
Order By: Relevance
“…Weight stigma has been associated with psychological distress [3], poorer mental health [4], disordered eating and unhealthy eating behaviours [5], substance use [6], more physiological stress [7], reduced motivation to engage in physical activity [8], additional barriers to weight loss maintenance [9], reduced healthcare seeking behaviour [10], and a higher risk for suicidality and mortality [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Weight stigma has been associated with psychological distress [3], poorer mental health [4], disordered eating and unhealthy eating behaviours [5], substance use [6], more physiological stress [7], reduced motivation to engage in physical activity [8], additional barriers to weight loss maintenance [9], reduced healthcare seeking behaviour [10], and a higher risk for suicidality and mortality [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Counter to traditional public health beliefs that social pressure encourages people with obesity to lose weight [ 25 ], ironically, evidence suggests that obesity stigma actually increases the risk of obesity. Obesity stigma may be associated with increased difficulty of losing weight and medication non-adherence and people with obesity may exclude themselves from some exercise settings [ 102 , 104 ]. Pearl and Puhl’s systematic review found that obesity self-stigma is associated with worse dietary adherence and reduced motivation and self-efficacy to complete health-promoting behaviours [ 105 •].…”
Section: Consequences Of Obesity Stigmamentioning
confidence: 99%
“…En este sentido, desde estudios en psicología y psicología de la salud se ha demostrado que la obesidad aparece a menudo acompañada del estigma de peso (Spahlholz, Baer, Konig, Riedel y Luck, 2016;Thedinga, Zehl y Thiel, 2021), fenómeno que se ha asociado a un aliciente para lograr un peso corporal reducido, basándose en la suposición que la vergüenza provocada por la estigmatización, motivaría a cambiar el comportamiento y lograría la reducción de peso a través de dietas autodirigidas y aumento del ejercicio físico (Rubino, Puhl y Dixon, 2020). Sin embargo, tanto estudios observacionales como aquellos experimentales, muestran que esas estrategias pueden surtir el efecto contrario y, en cambio, pueden inducir a evitar el ejercicio, consumir alimentos poco saludables y aumentar el comportamiento sedentario, llevando a una mala salud metabólica, mayor aumento de peso y reducción de la calidad de vida (Puhl y Suh, 2015).…”
Section: Introductionunclassified